Quality improvements of healthcare trajectories by learning from aggregated patient-reported outcomes: a mixed-methods systematic literature review - Maarten C. Dorr; K. S. van Hof; J. G. M. Jelsma; E. A. C. Dronkers; R. J. Baatenburg de Jong; M. P. J. Offerman; M. C. de Bruijne (BMC, 2022)
Key messages What is already known on this topic The aggregated patient-reported outcome measures (PROMs) can be used for analytical and organizational aspects of improving and regulating healthcare, but there is little empirical evidence regarding the effectiveness of aggregated PROMS. What this study adds This study adds a detailed overview of the types of quality improvement methods and recommendations for implementation in practice. How this study might affect research, practice or policy Researchers and policy-makers should consider the barriers, facilitators and lessons learned for future implementation and evaluation of quality improvement methods, as presented in this manuscript, to further advance this field.